MODEL PENDIDIKAN MULTIKULTURAL DI PESANTREN MODERN - Ahmad Farid; Siska Sri Suciyanti; Rahma Maulidiah; Rifa Wardatia Muntaha; Fitri Kusumaning Tyas; Melika Jihan; Sifta Hamidah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The activities carried out in Islamic boarding school are colored by their culture. Harmony between Santri and Kyai is characterized by a moral atmosphere that fosters character development, spiritual values, manners, and a rich circulation of manners. Apart from being one of the oldest educational institution in the caountry,Islamic boarding schools also play an important role in advancing national culture and upholding diversity, which is Indonesia’s unshakable national motto. What is instilled in the student is the ideal of harmony and peace from an islamic boarding school that applies contemporary educational methods. The diversity of modern Islamic boarding schools is caused by the diverse ethnic backgrounds and regional origins of the students. Thus, the topic of this research is intercultural education in the context of modern islamic boarding schools. After using the library research method, this research examined various reference materials, such as books, journals and articles. These findings provide an overview of interectual education in the context of modern islamic boarding schools